Single-sex versus Coeducational Schools: Which One is More Effective to Implement in Indonesia? - Jalaluddin, Jalaluddin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Single-sex school is the oldest educational institution in Indonesia and it is considered to be one of the original cultures of Indonesia. Although this schooling system has a big number in Indonesia, there have not been many investigations examining its effectiveness on the students’ performance. Therefore, this issue has a central role to guide the future implication of educational system in Indonesian high school. This investigation presents information on the effectiveness of single-sex school on the students’ performance in Indonesian high school context. Further, this investigation would also provide the relevancy of single-sex school with the Indonesian culture. In addition, this study would hopefully enhance the knowledge of other practitioners, students’ parents, as well as researchers about the position of local culture in the learning process.  It is argued that single-sex school is more effective to apply in Indonesia to improve the learners’ performance at school. It is highly supported by its wider relevance with the Indonesian culture. Examining three main points can proof this. Firstly, single-sex school is very potential to promote good learners’ behaviour. Secondly, learning in a single-gender school can increase the students’ gender satisfaction. Lastly, single-sex school is a safer place to learn any subject as opposed to coeducational school where not all subjects are suitable to teach.